Brainstorming Audit Team Based on Auditor's Interpersonal Skills in Detecting Fraud - Anton, Anton; Mowilos, Afni Feiby Megasilva (AJAR, 2025)
The purpose of this research is to empirically test the effect of audit team brainstorming based on the auditor's interpersonal abilities in detecting fraud in auditors at KAP Semarang City. The population in this study was 28 KAPs in Semarang City. The sampling technique uses non-probability sampling with a purposive sampling technique, namely a data source sampling technique with certain considerations. These considerations include auditors who work at KAP in Semarang City, work for at least one year, and are willing to fill out a questionnaire. From this sampling technique, a sample of 103 respondents was obtained. This research uses the Structural Equation Modeling (SEM) analysis method with LISREL 8.80 software. Based on the results of the hypothesis test, it can be concluded that the Auditor's Interpersonal Ability has a positive and significant effect on Fraud Detection. The Auditor's Interpersonal Ability has a positive and significant effect on the Audit Team's Brainstorming. Audit Team Brainstorming doesn’t have a positive and significant effect on Fraud Detection and the Auditor's Interpersonal Abilities does not have a positive and significant effect on Fraud Detection through Audit Team Brainstorming.